Numerical investigation of a longfin inshore squid's flow characteristics - Tabatabaei, Mahdi Malazi; Okbaz, Abdulkerim; Olcay, Ali Bahadir (PERGAMON-ELSEVIER SCIENCE LTD, 2015)
In the present paper, a numerical squid model was obtained from a real longfin inshore squid (Doryteuthis pealeii) using computed tomography (CT) images. Two-dimensional axisymmetric squid models were then generated with fineness ratios of 7.56, 6.20 and 4.39 to investigate viscous and pressure drag forces. The study examined the effect of a squid's nozzle diameter on squid swimming and jet velocities for the investigated models in the squid's Reynolds number range from 456,000 to 2,800,000. Velocity vector field around the squid's curvature body was analyzed to understand flow recirculating regions and make connection with the drag coefficient. It was documented that models with a fineness ratio of 7.56 and 6.20 showed streamlined body behavior while a fineness ratio of 4.39 model exhibited a blunt body appearance based on drag force and velocity vector results. The study also revealed that a larger nozzle diameter provided better propulsive efficiency and faster swimming velocity for the squid. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Longfin inshore squid; Computed tomography (CT); CFD; Propulsive efficiency; Viscous and pressure drag; Drag coefficient; DRAG; COEFFICIENTS; PERFORMANCE; Engineering; Oceanography